Celiac crisis with thrombocytopenia and coagulopathy in a child - Mazman, Duygu İskender and Dereci, Selim and Hızlı, Şamil and Doğan, Hayriye Tatlı and Ateş, Burcu Berberoğlu and Hızal, Gülin and Demir, Arzu Meltem and Aksu, Aysel Ünlüsoy (The Turkish Journal of Pediatrics, 2022)
Background. Celiac disease rarely presents with edema, hypoalbuminemia, acute metabolic deterioration, and electrolyte imbalances. This life-threatening condition is defined as a celiac crisis and may mimic disorders with metabolic derangement and sepsis. The crisis may present at onset or develop in celiac disease patients with poor compliance to a gluten-free diet. The fluid resuscitation and replacement of electrolyte deficits are life-saving modalities. Case. A 14-month-old girl was admitted with fever, lethargy, severe dehydration, edema, hypotension, and commenced sepsis therapy. However, the patient had a growth delay and loss of weight with diarrhea and delayed motor skills. On admission, laboratory evaluation showed anemia, coagulopathy, hypoalbuminemia, electrolyte disturbances, and metabolic acidosis and developed thrombocytopenia during follow-up. The celiac serological tests and upper gastrointestinal endoscopic duodenal mucosa appearance, and duodenum histopathology findings suggested celiac disease. Conclusions. This case highlights that a celiac patient may present with a severe illness like sepsis and may be associated with cytopenia and coagulopathy in the celiac crisis.